Assessment of trends in biological and behavioural surveillance data: is there any evidence of declining HIV prevalence or incidence in Malawi?. (30th March 2006) - Bello, G A; Chipeta, J; Aberle-Grasse, J
Abstract : Objectives: In 2003 an estimated 87 000 AIDS deaths and approximately 110 000 new infections occurred in Malawi. This paper aimed to analyse and review HIV prevalence trends in conjunction with other second generation surveillance data including behavioural data and, therefore, to describe trends in HIV prevalence and behaviours related to HIV transmission. Methods: In order to determine the extent of the problem, HIV prevalence in Malawi has been monitored through testing women attending antenatal clinics in 19 sentinel sites consistently since 1994. These sites are classified as urban, semi-urban, and rural. Results: The overall HIV prevalence for all 19 ANC sentinel sites in 2003 was 19.8% (95% CI 19.0% to 20.7%). The central region urban/semi-urban sites showed a decline in prevalence from 1999 to 2003. Since 1997, overall national incidence estimates remained stable. This stable incidence estimate is supported by the proxy of fairly stable prevalence in ANC attendees aged 15–24 years. HIV sentinel surveillance data for Lilongwe city showed a significant linear decline in prevalence (p<0.00001) over the last seven years for both all ANC attendees and those aged 15–24 years suggesting that incidence has declined over the time period. Conclusion: The available epidemiological and behavioural surveillance data show that HIV prevalence has declined in several urban and semi-urban areas, specifically in the central region with Lilongwe (capital of Malawi) showing exceptionally strong evidence of decline. In some rural areas, particularly in the northern region there is some evidence of an increasing trend in HIV prevalence.